2007
DOI: 10.3171/spi.2007.6.6.567
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture needles causing lumbar cerebrospinal fluid fistula

Abstract: Acupuncture is a frequently used adjuvant treatment for chronic pain conditions. The authors report the case of a patient in whom the delayed migration of embedded acupuncture needles into the lumbar spinal canal caused the formation of a cerebrospinal fluid fistula and spine-related headache. The needles were safely removed surgically and the patient improved clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…There were nine cases of central nervous system injury, including five spinal cord injuries [55, 7375, 77] and four of brain injury [56, 71, 72, 76]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were nine cases of central nervous system injury, including five spinal cord injuries [55, 7375, 77] and four of brain injury [56, 71, 72, 76]. …”
Section: Resultsmentioning
confidence: 99%
“…Two of the spinal injuries were caused by migrating broken needles [55, 75]; the others were probably the result of needling too deeply. All patients recovered after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Ulloth et al [12] reported a case of a CSF fistula caused by an acupuncture needle. In the present case, CSF leakage was observed immediately after removal of the needle.…”
Section: Discussionmentioning
confidence: 99%
“…The exact cause of the headache remains uncertain, but meningeal irritation due to the presence of a foreign body 12,13 is a plausible explanation, since there was no CSF leakage, which usually causes headache. 18,19 Nevertheless, no other signs of meningeal irritation were present. Only 1 case reported in the literature describes a headache (together with pain and stiffness) in a patient with a foreign body in the spinal canal.…”
Section: Discussionmentioning
confidence: 99%